Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.24996/ijs.2022.63.6.39
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Best Rainwater Harvesting System in Al-Muthanna Governorate, Iraq

Abstract: Rainwater harvesting is one of the available solutions to overcome water scarcity in arid and semi-arid regions with highly variable rainfall and unexpected periods of drought or floods. This study aims to identify the best rainwater harvesting system in Al-Muthanna governorate using Remote Sensing (RS) and Geographic Information System (GIS) techniques. Landsat 8 images were used to produce the land use map which shows five different classes: water (0.2%), bare soil (82.11%), built-up (15.71%), forest (0.27%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…station 3 in October of the same year. Figure(10). In water before treatment, the lowest value of sodium was recorded at 14.10 mg/L at Station 10 in October and the highest value at 90.0 mg/L at Station 9 in October 2022, while for water after treatment, the lowest value of sodium was…”
mentioning
confidence: 88%
“…station 3 in October of the same year. Figure(10). In water before treatment, the lowest value of sodium was recorded at 14.10 mg/L at Station 10 in October and the highest value at 90.0 mg/L at Station 9 in October 2022, while for water after treatment, the lowest value of sodium was…”
mentioning
confidence: 88%
“…The results of the statistical analysis, Table (4), indicated that the effect of bacterial biofertilizer, phosphorus sources, vermicompost and their interactions had a significant effect on increasing the dry weight of the shoot (meg ha -1 ). Compared to the fertilization treatmentThe biological and bacterial B0, which gave the lowest average dry weight of the vegetative total, amounted to 3.91 (meg ha -1 ), and the addition of phosphorous sources had a significant effect on increasing the dry weight of the vegetative total (meg ha -1 ), and the highest value was for the treatment of the rock phosphorus source Phosphate P2 by giving the highest value to the total dry weightThe vegetative value amounted to 5.…”
Section: Dry Weight Of Shoots (Meg Ha -1 )mentioning
confidence: 99%
“…Microorganisms have an important role in the distribution of phosphorus between the soil and plant systems, specifically in the rhizosphere, and Bacillus magaterium is the most efficient and most present in the soil Which converts phosphate from the unprepared form to the ready form. Also, these bacteria work to strengthen the plant's immunity against diseases through various mechanisms [4,5]. Phosphorus has a role in controlling the chemical and biological reactions of photosynthesis, respiration, and cell division, hence its importance for flowering, fruiting, seed IOP Publishing doi:10.1088/1755-1315/1262/8/082046 2 formation, and root growth and development [6,7].Vermicompost, an organic fertilizer, increases soil nutrients, growth regulators, and enzymes, increasing productivity, improving soil physical and mineral properties, and creating a safe food production ecosystem by reducing mineral fertilization, which harms public health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Rainwater harvesting (WH) is the oldest-to-newest technology for collecting water from natural catchment areas to increase the water amount accessible in certain places [1]. There has been renewed interest in WH in recent decades, due to the increasing water demand for agriculture and urban development resulting from rising pressure of population and change in climate.…”
Section: Introductionmentioning
confidence: 99%